Limitations of human t-lymphotropic virus type 1 antibody testing in hospitals of endemic regions in China - Chen, Yi; Chen, Yanxin; Zheng, Jing; Yang, Jiajie; Wu, Yong; Hu, Jianda; Wu, Zhengjun (Frontiers in Cellular and Infection Microbiology, 2025)
PurposeThis study aims to evaluate the sensitivity and specificity of human T-lymphotropic virus type 1 (HTLV-1) antibody testing within hospitals located in HTLV-1 endemic areas of China.MethodWe performed a retrospective analysis of the clinical records and laboratory results for 1,147 patients who underwent HTLV-1 antibody testing using the Wantai HTLV-1 antibody detection kit and Polymerase Chain Reaction (PCR) testing for HTLV-1 nucleic acids, at Fujian Medical University Union Hospital between 2017 and 2023.ResultThe study population comprised 674 males (58.8%) and 473 females (41.2%), with an age distribution ranging from 7 to 86 years, and a median age of 50 years. Of the patients, 81 (7.1%) tested positive for HTLV-1 antibodies, including 39 males and 42 females. Predominantly, these positive cases were identified within the hematology department (93.8%). The cases originated from several high-prevalence coastal regions in Fujian province, such as Pingtan Island, Fuqing, Changle, Lianjiang, Fuan, Shouning, Xiapu, Zhouning, Fuding, Jiaocheng, Xiuyu, and Licheng. According to current standards for interpreting positive results, only 79.6% of patients with adult T-cell leukemia/lymphoma (ATLL) confirmed by HTLV-1 nucleic acid testing presented positive antibody results. Comparison of HTLV-1 antibody and nucleic acid test results revealed that the antibody test possessed a sensitivity of 63.0% and a specificity of 94.8%. A receiver operating characteristic (ROC) curve analysis determined that a threshold of 0.335 signal-to-cutoff (S/CO) was optimal for classifying positive antibody test results, yielding a sensitivity of 86.3% and a specificity of 94.4%.ConclusionThe Wantai HTLV-1 antibody test kit, when utilized in hospitals within endemic regions, exhibits a high level of specificity. However, its sensitivity is found to be lacking when evaluated against the current standards for the interpretation of positive results. For patients with a high clinical suspicion of HTLV-1 infection-related diseases, it is crucial to conduct testing of HTLV-1 antibodies and nucleic acids.